Pengembangan Media Pembelajaran Berbasis Augmented Reality (AR) Pada Materi Momentum Kelas XI - Bachtiar, Bachtiar; Darsikin, Darsikin; N. Laratu, Wahyuni (Universitas Tadulako, 2024)
This study aims to develop and determine the validity and feasibility of Augmented Reality (AR)-based learning media in physics subjects. This study is a development research or Research & Development (R&D) using the ADDIE model (Analysis, Design, Development, Implementation, and Evaluate). The subjects of the study were 30 students of class XI-5 SMAN 7 Palu in the 2022/2023 academic year. The instrument used was a closed questionnaire with a Likert scale type. Based on the results of the assessment by material experts on AR-based learning media, the category was